Modeling of the Internal Temperature for an Energy Saving Chinese Solar Greenhouse - Yau, J.; Wei, J. J.; Wang, H.; Eniola, O.; Ibitoye, F. P. (Engineering, Technology & Applied Science Research, 2020)
The global rise in food demand requires urgent attention in the aspect of crop production. The microclimate of a greenhouse is a critical issue in agricultural practice, due to the variations of the external climatic conditions and their negative effect on crop production. In this work, a dynamic model of the internal air temperature of a Chinese solar greenhouse was designed in Matlab/Simulink environment. The dynamic model was designed with the use of energy balance equations. The weather data consisting of solar radiation, relative humidity, ambient temperature, and Photosynthetically Active Radiation (PAR) were acquired from meteorological stations. The results of the simulations show that the temperature of the internal air varies with weather conditions, location, number of covers, and the structure of the solar greenhouse.